Supervision Controls on Companies Concentration - Amer, Ahmed; Mohammed ِAkram (Journal of Legal Sciences, 2022)
The main objective of controlling companies Concentration is to prevent their potential anti-competitive effects on the competitive structure of the relevant market, in order to protect freedom of competition in it. In this context, it is necessary to verify that these operations do not impede effective competition or reduce it significantly by making it less than it was before, it is necessary to Anticipate all the effects In order to achieve the goal of controlling on it and revealing their potential restrictive effects. So there must be Auditing Norms that enable the authorities entrusted with the protection of competition and the prevention of monopolistic practices to evaluate these effects and determine their positive and negative aspects. This study sheds light on the Controls on Companies Concentration by studying American and European law and comparing it with Iraqi law.